Personality and coping. What traits predict adaptive strategies? - Melendez, Juan C.; Satorres, Encarnación; Delhom, Iraida (Anales de Psicología / Annals of Psychology, 2020)
Coping and strategies used play an essential role in the adaptation to changes, and personality traits are important predictors of these strategies. The aim of this study is to find out what traits predict different coping strategies in older adults. Participants were 226 older adults (60 to 88 years old). Data on personality and coping strategies were obtained through the NEO-FFI and the Coping Strategies Questionnaire. Multiple linear regression models were conducted. Neuroticism positively predicted emotion-oriented strategies: negative self-focused, overt-emotional expression, avoidance, and religious. Problem-oriented strategies were positively predicted by openness to experience (problem-solving focused), agreeableness (positive reappraisal), and conscientiousness (problem-solving focused and positive reappraisal). In addition, agreeableness and conscientiousness negatively predicted emotion-oriented strategies: overt-emotional expression and negative self-focused. Extraversion did not predict any coping strategy. These findings show that neuroticism is a maladaptive trait during aging, whereas openness to experience, agreeableness, and conscientiousness are adaptive traits in older adults.